(3Gdbhd GdhGaj HTQM GdcGais - (3YHO GdHQ Hf YHO GdbGOQ Hf eMeO Gdajheis; (3TgGH GdOjf CHh GdYHGS CMeO Hf YHGO Hf TYjH GdUCHj GdbGgQj GdTGaYj, GdNhGU,J (B858 (3g` s ((3eQJVi Hf eUWai Hf MSf GdcQOi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO ajbhd YHO GdHQ Hf YHO GdbGOQ deG QCjJ eJf GdcGai ai Ydei GdYQhV hGdbhGai GdPi gh dWdGH gPG Gdaf cGai eMJGL dTQM jMd eHGfjg GdaGFbI s
(3BNQgG (B:s
(3hCf jdgL GddSGf HEJaGb GdLfGf TGcQkG Ydi eRjO GdEfYGe def jSQ dg CSHGH GdEfYGe QGLjkG ef YhGFO aVdg MSf GdNJGe s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdYQhV hGdbhGais